Leadership and Institutional Design in Public Service Digitalization - Suri, Dia Meirina; Amri, Pahmi; Hildawati, Hildawati (Universitas Padjadjaran, 2024)
Digitalization of public services has become an influential agenda for the government in today's digital era. However, to succeed in this digital transformation, institutions and leaders face challenges, such as unpreparedness of infrastructure and resources and mismatches between regulations and policies. This study analyzes and explains the appropriate leadership and institutional design in digitalizing public services. The method used is a case study approach with data collection using interviews with research informants. The results of the interviews are processed using the Nvivo 12 Plus data processing application and analyzed qualitatively. The results found that leadership and institutional roles are interrelated and influence each other in digitalizing public services. Robust leadership design in vision and strategy, building a culture of innovation, along with institutional design that can organize, facilitate collaboration, and manage organizational change, form a solid foundation for the success of digitizing public services. However, these changes must be balanced with continuous evaluation to refine and improve digital services. This research is expected to contribute to the government in facing challenges in implementing the digitalization of public services, especially in leadership and institutional design.